Wnt pathway modulation generates blastomere-derived mouse embryonic stem cells with different pluripotency features - Vila-Cejudo, Marta (J Assist Reprod Genet, 2020)
PURPOSE: This study aimed to determine the role of Wnt pathway in mouse embryonic stem cell (mESC) derivation from single blastomeres isolated from eight-cell embryos and in the pluripotency features of the mESC established. METHODS: Wnt activator CHIR99021, Wnt inhibitor IWR-1-endo, and MEK inhibitor PD0325901 were used alone or in combination during ESC derivation and maintenance from single blastomeres biopsied from eight-cell embryos. Alkaline phosphatase activity, FGF5 levels, expression of key pluripotency genes, and chimera formation were assessed to determine the pluripotency state of the mESC lines. RESULTS: Derivation efficiencies were highest when combining pairs of inhibitors (15–24.7%) than when using single inhibitors or none (1.4–10.1%). Full naïve pluripotency was only achieved in CHIR- and 2i-treated mESC lines, whereas IWR and PD treatments or the absence of treatment resulted in co-existence of naïve-like and primed-like pluripotency features. IWR + CHIR- and IWR + PD-treated mESC displayed features of primed pluripotency, but IWR + CHIR-treated lines were able to generate germline-competent chimeric mice, resembling the predicted properties of formative pluripotency. CONCLUSION: Wnt and MAPK pathways have a key role in the successful derivation and pluripotency features of mESC from single precompaction blastomeres. Modulation of these pathways results in mESC lines with various degrees of naïve-like and primed-like pluripotency features.